Key Insights into Respiratory Virus Testing: Sensitivity and Clinical Implications - Julio Garcia-Rodriguez; Frédéric Janvier; Clemens Kill (Microorganisms)
Acute respiratory infections are a significant challenge in primary care and hospital settings. Viruses are the most common etiology and the overlapping symptomatology among major respiratory viruses, such as influenza, severe acute respiratory syndrome coronavirus 2, and respiratory syncytial virus, requires the use of diagnostic tests that deliver early and accurate results. With the increasing availability of rapid antigen tests (RATS), it is tempting to prefer them over polymerase chain reaction (PCR) tests. However, compelling arguments support the existing recommendations in some European countries to maintain PCR testing for patient management throughout the year. RATs show sensitivities below 30% with lower viral loads, which are common and can have significant clinical implications. RATs perform well at lower cycle threshold (Ct) values, with sensitivity reaching 97.9% for Ct values below 20, which drops significantly for values above 25. Factors affecting viral load include disease stage, vaccination status, and viral variants, all of which can compromise the accuracy of antigen tests. Multi-target PCR tests effectively overcome these issues, ensuring reliable diagnosis. Additionally, the early detection of paucisymptomatic cases is essential in primary care and hospital settings to facilitate isolation and prevent secondary infections. Economic analyses support the use of comprehensive PCR tests, such as triplex-type tests, detecting SARS-CoV-2, influenza viruses, and RSV, as a first-line approach, as they can reduce case numbers and healthcare resource utilization. Maintaining PCR testing year-round is therefore crucial for the effective management of respiratory infections.